Fundamental Constants Evaluating Measurement Uncertainty - Menin, Boris M. (Cambridge Scholars Publishing, 2019)
The book is devoted to one of the important areas of theoretical and experimental physics--the calculation of the accuracy of measurements of fundamental physical constants. To achieve this goal, numerous methods and criteria have been proposed. However, all of them are focused on identifying a posteriori uncertainty caused by the idealization of the model and its subsequent computerization in comparison with the physical system. This book focuses on formulating an a priori interaction between the level of a detailed description of a material object (the number of registered quantities) and th.